(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
In this article, the characteristics of archaic syncretism and their influence in Uzbek ethnocultural and national culture are revealed in a scientific-analytical, scientificdiscussive way. In this, the syncretic features, important signs and social significance of the processes related to archaic syncretism in the Uzbek ethnoculture and national culture are expressed in a scientific and analytical way